Chemical constituents and biological activities of Calophyllum inophyllum L. and Calophyllum soulattri burm. ex F. mull - Mah, Siau Hui (2012)
A chemical investigation of the stem bark of Calophyllum inophyllum and Calophyllum soulattri was carried out using various chromatographic and recrystallization techniques. All of the secondary metabolites successfully isolated were structurally characterized on the basis of spectroscopic evidence, such as 1D and 2D NMR, MS, IR and UV. Several biological assay screenings were also conducted on the crude extracts and pure metabolites. Extensive chromatographic techniques applied to the dichloromethane extract of the stem bark of Calophyllum inophyllum resulted in two new xanthones, namely inophinnin (208) and inophinone (209), along with three other xanthones, pyranojacareubin (132), rheediaxanthone A (213), and macluraxanthone (62) and, a sterol, stigmasterol (207). The ethyl acetate extract of C. inophyllum gave a simple xanthone, which is 4-hydroxyxanthone (63). In addition, two terpenoids, friedelin (4) and betulinic acid (205), as well as a sterol, lupeol (206), were also isolated from the non-polar n-hexane extract. Meanwhile, the stem bark of Calophyllum soulattri afforded two new xanthones, soulattrin (210) and phylattrin (211), and a new coumarin, soulamarin (212). Both new xanthones were isolated from the dichloromethane extract, together with four other xanthones, macluraxanthone (62), caloxanthone C (52), brasixanthone B (123) and trapezifolixanthone (14), a coumarin, calanolide E (80), and a sterol, stigmasterol (207). On the other hand, one new coumarin was obtained from the hexane extract, which also contains a sterol, β-sitosterol (18), and a terpenoid, friedelin (4). Structural modifications were achieved using the acetylation process on two major constituents, namely, phylattrin (211) and macluraxanthone (62). The outcome was the successful conversion of the hydroxyl groups in the molecules into acetyl groups for both compounds. The acetylation reaction of phylattrin (211) and macluraxanthone (62) gave one and two acetate-substituted products, respectively. Cytotoxicity screening (MTT Assay) was carried out on all of the crude extracts and pure compounds using nine human cancer cell lines, SNU-1 (stomach), HeLa (cervical), NCIH23 (lung), Hep G2 (liver), K562 (leukemia), Raji (lymphoma), LS174T (colon), SKMEL-28 (skin) and IMR-32 (neuroblastoma) cells. A new xanthone, soulattrin (210), exhibited strong anti-proliferative activity against all of the cell lines with IC50 values less than 1.25 μg/mL, except for the Hep-G2 cell line. Macluraxanthone (62) also showed significant cytotoxic effects against all of the cell lines with IC50 values less than 2.74 μg/mL, except for the Hep-G2, LS174T and IMR-32 cell lines. Another two new xanthones, phylattrin (211) and inophinnin (208) are considered as strong cytotoxic agents of the HeLa, SNU-1 and NCI-H23 cell lines (IC50 values of 3.90, 4.15 and 4.43 μg/mL, respectively), and HeLa cell line (IC50 value of 3.90 μg/mL), respectively. Caloxanthone C (52) possessed high inhibition rate against the Hep-G2 (IC50 value of 2.35 μg/mL) and HeLa (IC50 value of 2.60 μg/mL) cell lines. 4-Hydroxyxanthone (63), trapezifolixanthone (14), and calanolide E (80) were found to have strong cytotoxicity against the HeLa cell line with respective IC50 values of 2.54, 2.86 and 2.86 μg/mL. In addition, pyranojacareubin (132) and betulinic acid (205) possessed strong activity against the K562 and SK-MEL-28 cell lines, respectively. Stigmasterol (207) gave low IC50 values of 0.17 and 3.90 μg/mL with respect to Raji and SK-MEL-28 cells indicating strong cytotoxic effects. Kaempferol and quercetin were used as standard drugs for comparison purposes of all these results. Antioxidant properties of the crude extracts and pure compounds were tested using the DPPH (2,2-diphenyl-1-picrylhydrazyl) radical scavenging method, and ascorbic acid was chosen as the standard agent. The results showed that the polar crude extracts exhibited higher activities with lower EC50 values. In other words, the methanol extracts for both plants showed the strongest activity, followed by the ethyl acetate and dichloromethane extracts. The non-polar n-hexane extracts were inactive. Among the pure compounds, soulattrin (210) and macluraxanthone (62) indicated strong activities with the same IC50 value of 11.72 μg/mL. Also, the total phenolic contents of all the crude extracts were measured using the Folin-Ciocalteu method and the methanol extracts of Calophyllum soulattri and Calophyllum inophyllum possessed the highest values of 460.7 and 426.4 μg/mL GAE, respectively, which contributed partly to the antioxidant activity. Anti-inflammatory assay was carried out using the nitric oxide (NO) assay method and this revealed that both hexane extracts possessed the highest percentage of inhibition of NO. The new xanthone, inophinnin (208), together with macluraxanthone (62), showed strong activities in the assay with the IC50 values of 23.91 and 8.82 μg/mL. Lastly, antibacterial tests were also carried out using four Gram positive and four Gram negative bacteria on the Calophyllum inophyllum extracts. The hexane and methanol extracts indicated some activities against the Gram positive bacteria, Bacillus cereus, Micrococcus luteus, Methicillin-sensitive Staphylococcus aureus (MSSA), and Methicillin-resistant Staphylococcus aureus (MRSA).